Prosthodontic Management of a Patient with Ectodermal Dysplasia: Case Report - Nejabi MB; Anwari A; Shadab H; Mtawakel N; Omarzad F; Ahmadi ME (Dove Medical Press, 2023)
Mohammad Bashir Nejabi,1 Abdurrahman Anwari,2 Hassina Shadab,3 Nargis Mtawakel,1 Fariha Omarzad,1 Mohammad Eissa Ahmadi3 1Prosthodontics Department, Kabul University of Medical Sciences (KUMS), Kabul, Afghanistan; 2Operative/ Restorative Dentistry and Endodontics Department, Kabul University of Medical Sciences (KUMS), Kabul, Afghanistan; 3Periodontics Department, Kabul University of Medical Sciences (KUMS), Kabul, AfghanistanCorrespondence: Abdurrahman Anwari, Operative/ Restorative Dentistry and Endodontics Department, Kabul University of Medical Sciences (KUMS), Jamal Mena, 3rd District, Kabul, Afghanistan, Tel +93795125522, Email yammamyama@gmail.comAbstract: Ectodermal dysplasia (ED) is an inherited disorder that affects the ectoderm of a developing embryo and impacts structures that originate from it. It typically presents as a triad of missing teeth (anodontia/hypodontia), sparse hair (atrichosis/hypotrichosis), and lack of sweat glands (hypohidrosis), often accompanied by nail dystrophy and palmoplantar hyperkeratosis. There are two main types of this condition: X-linked anhidrotic or hypohidrotic and hidrotic (autosomal type). The oral manifestation of ED may include anodontia or hypodontia, with or without cleft lip and palate. Tooth loss leads to a decrease in the height of the alveolar ridges, resulting in a reduction of the vertical dimension of the lower face, disappearance of the vermilion border, and prominent lips. As a result, the affected person's face may resemble that of an elderly individual. The current case report aims to illustrate the prosthodontic rehabilitation of 16-year-old male patient with ectodermal dysplasia and complete anodontia, visiting Dentistry Teaching Hospital, Kabul, Afghanistan. Fortunately, this patient was acceptably managed with the collaboration of several disciplines.Keywords: prosthodontic management, ectodermal dysplasia, anodontia, case report